MANAGING COMMUNICATIVE CLASSROOM - o‘g’li, Shoxobiddinov Sirojiddin Isomiddin (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
It is researched in this work, the teaching of communicative language and its effective ways as well as managing communicative classroom and how to contact with students. It is also highlighted the effective use of communicative language teaching methods and techniques while teaching. Information is provided about the current focus and importance of foreign language teaching.